Neuroprotective natural products against experimental autoimmune encephalomyelitis: A review. (October 2019) - Mohtashami, Leila; Shakeri, Abolfazl; Javadi, Behjat
Graphical abstract: Image 1 Highlights: Natural products have opened new horizons in treating multiple sclerosis. Improving demyelination and inflammation is among the key therapeutic mechanisms. Further clinical trials are essential to approve the results of animal studies.